Eugene Onegin - Cajkovskij, Pëtr Il'ic (Decca, 2001)
Petr Weigl's beautiful film evokes superbly this most atmospheric of operas, whils Sir Georg Solti captures both the passion and subtlety of Tchaikovsky's magnificent score. The golden-voiced Teresa Kubiak sings the innocent Tatyana, Stuart Burrows is the ill-fated Lensky, and Bernd Weikl is Eugene Onegin, whose arrival is destined to change everybody's lives. [www.dvdera.com]